2022
DOI: 10.1111/1541-4337.12987
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive overview of emerging processing techniques and detection methods for seafood allergens

Abstract: Seafood is rich in nutrients and plays a significant role in human health. However, seafood allergy is a worldwide health issue by inducing adverse reactions ranging from mild to life-threatening in seafood-allergic individuals. Seafood consists of fish and shellfish, with the major allergens such as parvalbumin and tropomyosin, respectively. In the food industry, effective processing techniques are applied to seafood allergens to lower the allergenicity of seafood products. Also, sensitive and rapid allergen-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 104 publications
0
3
0
Order By: Relevance
“…Parvalbumin and tropomyosin are also allergens in shellfish. It was demonstrated that tropomyosin causes a high cross-reactivity in crustaceans, insects, and other molluscs [15]. Peanuts and tree nuts pose a safety risk because could trigger fatal anaphylaxis even in small amounts.…”
Section: Allergens Of Traditional Foodmentioning
confidence: 99%
“…Parvalbumin and tropomyosin are also allergens in shellfish. It was demonstrated that tropomyosin causes a high cross-reactivity in crustaceans, insects, and other molluscs [15]. Peanuts and tree nuts pose a safety risk because could trigger fatal anaphylaxis even in small amounts.…”
Section: Allergens Of Traditional Foodmentioning
confidence: 99%
“…Parvalbumin and tropomyosin are also allergens in shellfish. It was demonstrated that tropomyosin causes a high crossreactivity in crustaceans, insects and other molluscs [15]. Peanuts and tree nuts pose a safety risk because they could trigger fatal anaphylaxis even in small amounts.…”
Section: Allergens Of Traditional Foodmentioning
confidence: 99%
“…The detection of allergens in food products can be pursued through different analytical approaches, the main being immunoanalytical, mass-spectrometry, nucleic-acid-based methods, and biosensors [ 6 , 7 ]. Laboratory methods are generally very sensitive and accurate; however, they are often laborious, time-consuming, expensive, and require experienced personnel and well-equipped laboratories.…”
Section: Introductionmentioning
confidence: 99%